IMPROVING STUDENTS’ MATHEMATICAL PROBLEM SOLVING ABILITY BY USING MACROMEDIA FLASH ON GEOMETRY MATERIALS - Muhammad Yani; Fatemah Rosma; Cut Mawar Helmanda (MATEMATIKA DAN PEMBELAJARAN, 2022)
The purpose of this study was to determine and describe the increase in students' mathematical problem solving abilities after receiving learning using macromedia flash at MTsN Model Banda Aceh. This research approach quantitatively through a quasi-experimental design and one group pretest posttest design. The population was all students of class VIII MTsN Model Banda Aceh, while the sample was selected using random sampling technique and selected students of class VIII-5 as the sample. The research data were collected through a mathematical problem solving ability test which included pretest and posttest questions. Furthermore, the data were analyzed through SPSS version 17 with paired sample t-test and percentage tests. The results showed that there was an increase in students' mathematical problem solving abilities after receiving learning using macromedia flash on geometry material at MTsN Model Banda Aceh. While the increase in students' mathematical problem solving abilities in understanding problems is 41.6%, planning problem solving is 47.2%, carrying out problem solving is 58.3%, and re-examining problem solving is 41.7%. The use of macromedia flash on geometry material is the right solution in visualizing abstract geometric objects into concrete forms, thereby accelerating the achievement of better students' mathematical abilities.